The Results of Medical Examination and Treatment Under The Impact of The Medical Equipment System at Central Public Hospitals in Vietnam - Nguyen, Nga Phuong (The journal of contemporary issues in business and government, 2022)
This study analyzes the medical equipment system's impact on patients' disease progression after being treated at Vietnamese central public hospitals. The study surveyed medical staff and patients treated at central public hospitals. The gathered information and assessment was used to evaluate the current state of medical equipment being used in hospitals. The study also compared the relationship between the medical equipment status and the change in health status after the treatment. Research shows that, although the socialization policy offers a good opportunity for hospitals to upgrade medical equipment, the current policies cause many hospitals to face legal problems and prevent patients from accessing higher treatment qualifications. Improving the health financing policy will thus improve central hospitals in providing healthcare services and create better conditions for Vietnamese people to access the health care system.